2020
DOI: 10.1016/j.matt.2020.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Domino-Driven Synthesis of Hollow Hybrid Carbon Spheres with Ultrafine Metal Nitrides/Oxides

Abstract: We have demonstrated an ingenious one-pot aqueous domino-driven synthesis toward hollow hybrid spheres with ultrafine metal nitrides/oxides in hollow carbon cavity. The micelle-interfacial copolymerization is applied for shell formation, while the copolymerization-generated H + spontaneously triggers oxometallate condensation for encapsulation. By regulating the synthetic conditions, the encapsulated metal species can be well tailored with different sizes/contents (nanocluster to several nanometers) and compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 69 publications
0
21
0
Order By: Relevance
“…S(1) in the ESM) for EE-MoS2 ( Fig. 4(e)), respectively, suggesting the simultaneous presence of diffusiondominated and capacitive contributions to capacity [40][41][42]. Whereas the b values of peaks A and C are 0.91 (diffusiondominated and capacitive contributions) and 1.13 (only capacitive contribution) for ED-MoS2 (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…S(1) in the ESM) for EE-MoS2 ( Fig. 4(e)), respectively, suggesting the simultaneous presence of diffusiondominated and capacitive contributions to capacity [40][41][42]. Whereas the b values of peaks A and C are 0.91 (diffusiondominated and capacitive contributions) and 1.13 (only capacitive contribution) for ED-MoS2 (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…However, solid carbon nanospheres may suffer from the large volume expansion caused by the repeated potassiation/depotassiation of K + , which will lead to poor electrochemical stability. For this reason, design of hollow carbon nanospheres becomes an attractive method to promote the electrochemical performance, 119,120,129,131 because hollow carbon nanospheres can not only facilitate the stability of electrode materials for providing space for the volume expansion, 132 but also accelerate kinetics by shortening the ionic diffusion distance. 133,134 For example, Bin et al 130 reported that the hollow carbon nanospheres showed a lower charge-transfer impedance and improved battery performance comparing with solid carbon nanospheres, indicating a hollow structure was in favor of fast metal ion transportation kinetics.…”
Section: Construction Of Zero-dimensional (0d) Nanostructurementioning
confidence: 99%
“…And they show inadequate capability to rationally manipulate ultrafine nanoparticles (e.g., down to nanocluster) with adjustable content and compositional complexity, thus far restricting their potentials for highly efficient K + storage. Recently, Xu et al 131 reported a versatile, general, and template-free synthesis of uniform hollow hybrid carbon nanospheres with various encapsulated ultrafine metal nitrides/oxides down to nanocluster scale, such as vanadium nitride (VN), vanadium oxide, molybdenum nitride, tungsten nitride, and bimetal-based nitrides. This was accomplished by onepot aqueous solution chemistry with well-orchestrated domino-driven reactions; the micelle-interfacial copolymerization was applied for the polymeric shell formation, and meanwhile, the copolymerization-generated H + spontaneously triggered oxometallate condensation inside micelles for encapsulation (Figure 10B).…”
Section: F I G U R Ementioning
confidence: 99%
“…To reduce the usage of fossil fuels and sustainably develop renewable energy utilization, e.g., solar energy and wind energy, advanced energy storage systems (such as batteries and supercapacitors) are in high demand [1][2][3][4]. For example, lithium-ion batteries (LIBs) have seen tremendous success as one of the most common types of power source in the portable electronics market, due to their high energy density [5][6][7]. However, the fire risk of the flammable organic electrolyte, high cost, as well as limited reserves of lithium, severely restrict the largescale implementation of LIBs in automotive and stationary storage applications [8,9].…”
Section: Introductionmentioning
confidence: 99%